Association and Mechanisms of Proton Pump Inhibitors Use with Type-2 Diabetes Mellitus Incidence in Adults: A Systemic Review and Meta-Analysis - Chenchula, Santenna; Sharma, Phulen; Ghanta, Mohan K.; Amerneni, Krishna Chaitanya; Rajakarunakaran, Padmavathi; Saggurthi, Pavani; Chandra, Madhu Bhargavi; Gupta, Rupesh; Chavan, Madhavrao (Current Diabetes Reviews, 2024)
Background: Proton pump inhibitors (PPIs) are an extensively prescribed class of anti-ulcer drugs. This systematic review aimed to investigate the association between PPI use and the risk of new-onset diabetes mellitus or type 2 diabetes (T2DM) incidence. Methods: A comprehensive literature search was conducted in PubMed, Scopus, Cochrane Library, and ClinicalTrials.gov using the search terms “proton pump inhibitor,” “proton pump inhibitors,” “PPIs,” “diabetes mellitus,” and “type 2 diabetes” from inception to February 2023. Statistical analyses were performed using the “Review Manager 5.4” version, and a statistically highly significant P-value <0.05 was set. Results: This systematic review identified 12 studies (8 cohort, 1 RCT, and 3 case-control) with a total of 12, 64, 816 population, and the median age ranged from ≥18 yrs to ≤ 75 yrs. The pooled relative risk (RR) observations of a random-effects meta-analysis model showed that chronic exposure to PPI use has a significant association with T2DM risk incidence (RR, 2.44; 95% confidence interval, 1.31–4.54; I2 = 99%, P < 0.00001). The systematic review findings of the three case-control studies also supported an association of dose-dependent and chronic use of PPIs with an incidence of T2DM among chronic users. Conclusion: The systematic review concludes that chronic PPI exposure increases the risk of T2DM incidence. The authors recommend the shortest possible duration of PPI use and not prescribing PPIs to high-risk prediabetics and those without a compelling indication for PPI use. Regular education to patients regarding adverse reactions with prolonged use may decrease the risk of adverse effects associated with PPIs. The authors suggest that gut dysbiosis, hypergastrinemia, hypomagnesemia, decreased pancreatic secretions and IGF-1 levels, and PXR activation associated with chronic acid suppression among chronic PPI users and the potency of PPIs might explain the association between abnormal glucose metabolism and T2DM incidence. Finally, the authors recommend further randomized controlled trials to investigate the association between PPIs and the risk of new-onset T2DM incidence.
Keywords: chronic use